(untitled) (Journal of Contemporary Philology, 2021)
In this paper I analyze the queering of time in Marcel Proust’s novel Sodom and Gomorrah, the fourth volume of In Search of Lost Times, focusing on the role the myth of the Fall plays as a catalyst of this process. I argue that the ambiguous intertwining of temporality and sexuality introduced by the myth of the Fall through the narration of Sodom and Gomorrah structures the narrativization of sexuality and temporality in the novel. In my analysis, queer times in Proust’s novel emerge at those instances when non-normative desires and practices result in the complexification of the dimensions of time. The inducement of temporal dissonance through queer forms of sexuality and sociability as motivated by the failure the Fall brings is done through writing. In this essay, the act of writing for Proust is addressed as a dimension of queer time.